Comparison of Mortality Incidence Between Fgsi Score and Procalcitonin Level in Fournier’s Gangrene in Tertiary Hospital - Budaya, Taufiq Nur; Rahmadian, Aldilla Wahyu (International Journal of Psychosocial Rehabilitation, 2020)
Fournier’s gangrene was defined as a high mortality rate disease which most of the cases detected in late phase resulting on poor prognosis. Several method promoted to predict mortality such as Fournier’s Gangrene Severity Index (FGSI) score and study of procalcitonin level. We compare the mortality incidence using both methods. The 32 cases collected from medical record and devided into survivor and non survivor group. Retrospectively evaluated the procalcitonin level and score of FGSI each group and analized using cross sectional comparison.Total of 32 cases collected from medical record database, starting January 2012 untill December 2016. All cases was presented in male patients ranging from 18 - 82 years old (mean 51,10 SD + 15,1). Identified score of FGSI > 9 was 59,45% (19 cases), and identified high level of procalcitonin was 99,97% (31 cases). Mortality incidence was 62,5% from all cases, which all the non survivor showing high level of procalcitonin and 80% (16 cases) showing score of FGSI > 9. In other hand, patients with high level of procalcitonin has 64,52% mortality incidence (20 cases) while patients with score of FGSI > 9 has 84,21% mortality incidence (16 cases). From survivor group 8,33 % (1 cases) showing normal level of procalcitonin and 75% (9 cases) showing score of FGSI < 9. Fournier’s gangrene are most common in male patients with high mortality rate. Procalcitonin level study and FGSI score evaluation are both able to predict the mortality. Procalcitonin showing higher senstivity while FGSI more specific in prediction.